Culinary Experience and Destination Choice: Examining the Influence of Tourist Lifestyle and Local Food Authenticity in Kerinci - Gampo Haryono; Reni Yuliviona; Kasman Karimi (Institut Agama Islam Negeri Kerinci, 2026)
Purpose: This study examines the influence of tourist lifestyle and local food authenticity on destination choice in Kerinci Regency. It also explores the role of culinary experience in shaping tourists’ decisions when selecting travel destinations. The study offers novelty by integrating tourist lifestyle and authentic local food within the context of culinary experience in an emerging culinary tourism destination. Design/Methodology/Approach: This research employs a quantitative approach using a survey method involving domestic tourists visiting Kerinci Regency. Respondents were selected using purposive sampling. Data were collected through structured questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS. Findings: The results show that tourist lifestyle plays an important role in influencing destination choice. Local food authenticity also contributes positively to tourists’ decisions in selecting Kerinci as a travel destination. In addition, both tourist lifestyle and local food authenticity significantly influence culinary experience. Culinary experience positively affects destination choice and serves as a mediating variable, strengthening the relationship between tourists' lifestyle, local food authenticity, and destination choice. Research Implications: The findings highlight the importance of developing authentic culinary tourism that aligns with tourists’ lifestyles to enhance destination attractiveness. Tourism stakeholders and local governments are encouraged to promote local culinary identity and create memorable dining experiences to strengthen Kerinci Regency’s position as a competitive tourism destination.